Community Empowerment through Participatory Planning: experiences of a mining town in Korea - 심재만 (한국농촌경제연구원, 2006)
This research paper examines the interactions between planning practices aiming for the developmental reconstruction of a local society and actual changes onto the society. For the purpose, the research measures four procedural characteristics in the voluntary planning practice in a declining mining town; it also analyzes three dimensions of community empowerment in the mountainous town Churam. The paper demonstrates that each characteristics of the four procedural variables in planning practices contributes to the relative dimensions of community empowerment, and that each one of the three dimensions of community empowerment exerts an influence on the constitution of actual planning practices, reversely. Based on the case study, the paper concludes that there exists a mutual causality between planning practices and social development, depending on participatory measures for local people in the planning processes. Drawing on the conclusion, the paper suggests the significance of participatory planning processes in socio-political reconstruction of local communities; by the same token, it also legitimizes the understanding of local governments’ public planning not only as an economic enterprise but also as a socio-political one.
Keywords: planning process; participatory planning; local community; community empowerment; mining town; planning process; participatory planning; local community; community empowerment; mining town